DOI: 10.14393/ufu.di.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Governança corporativa e a distribuição de dividendos no setor bancário brasileiro

Abstract: Primeiramente agradeço a Deus pela vida, pela família e pela oportunidade de estudar e aprender. Agradeço aos meus pais e ao meu irmão, pelo constante incentivo aos estudos, por serem também exemplos de esforço e determinação e por compreenderem a minha ausência durante o curso. Agradeço também aos colegas de classe pelas contribuições aos trabalhos realizados em sala e pelo apoio nos momentos difíceis ao longo do curso. Agradeço à orientadora Prof.ª Dr.ª Kárem Ribeiro e ao co-orientador Prof. Dr. Marcelo Fodr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…On the other hand, the LEV and SIZE variables were significant at 1% and both negatively correlated to the dividend distributed, when measured by the DY proxy. These results corroborate the findings of Souza, Peixoto and Santos (2016) and Paiva, Ribeiro and Fodra (2016). Souza et al (2016) who also found a negative and significant relationship between financial leverage and distributed dividends.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the LEV and SIZE variables were significant at 1% and both negatively correlated to the dividend distributed, when measured by the DY proxy. These results corroborate the findings of Souza, Peixoto and Santos (2016) and Paiva, Ribeiro and Fodra (2016). Souza et al (2016) who also found a negative and significant relationship between financial leverage and distributed dividends.…”
Section: Discussionsupporting
confidence: 90%